Comparative analyses of Nigerian and US corn Stalks, using PY-GC/MS - Eseyin, Anthonia E.; Hassan, El Barbary; El-Giar, Emad, M (International Journal of Advanced Chemistry, 2015)
Pyrolysis gas chromatography mass spectrometry (Py-GC/MS) studies were carried out on the Nigerian and US corn stalks at 500 Â°C. Analyses of the fast pyrolysis products showed that the Nigerian corn stalks produced more diverse compounds like: acetaldehyde, acetic acid methyl ester, 2,3-pentanedione, 1-hydroxy-2-butanone, butanedial, phenol and vanillin. On the other hand, the pyrolyzed US corn stalks produced compounds like: furfural, phenol, 2-methoxy, 2-methylbenzaldehyde, and 2-methoxy-4-vinylphenol which had significantly high peak area percentages. Few anhydrous sugars were detected in the pyrolysis products of both samples. Both samples were found to be good biomass for the production of bio-oil and chemicals. However, the Nigerian corn stalks seem to be more suitable for the production of bio-oil while the US corn stalks seem to be more suitable for the production of valuable chemicals.